Multidimensional Scaling - Based Framework for Assessing the Sustainability of Communal Wastewater Treatment System - Rinda Meylia Widyasari; Anthon Efani; Dini Atikawati; Hari Wahyu Wijayanto (Indonesian Journal of Environmental Management and Sustainability, 2026)
This study evaluates the sustainability of a communal wastewater treatment plant (CWWTP) in Pohjentrek Village, Pasuruan City, Indonesia, by integrating across five dimensions, technical, social, economic, environmental, and institutional using Multi-Dimensional Scaling (MDS), complemented by leverage and Monte Carlo analyses to identify critical attributes and validate model robustness. The results show that the social and environmental dimensions achieved a very sustainable status, with index values of 82.71 and 82.40, respectively. These findings reflect strong community acceptance of the communal wastewater treatment system and recognition of its environmental benefits, particularly in reducing potential groundwater contamination in densely populated residential areas. In contrast, the technical (67.38), economic (74.02), and institutional (72.10) dimensions were classified as sufficiently sustainable, indicating that the system remains operational but exhibits several structural vulnerabilities. Technical sustainability is constrained by effluent quality that has not yet consistently met regulatory standards and by the absence of routine effluent monitoring. While economic sustainability remains highly dependent on limited household contributions due to the absence of other funding source. Institutional sustainability largely relies on the commitment of local managers. The reliability of the sustainability assessment is supported by low stress values (0.14–0.15), high coefficients of determination (R² = 0.94–0.95), and Monte Carlo deviations below 5%, indicating a stable and statistically robust MDS configuration. Importantly, the sustainability classification reflects the aggregated performance across multiple dimensions rather than relying solely on individual indicators such as effluent compliance. This study contributes to the literature on sanitation sustainability by providing a validated, attribute-level sustainability diagnosis that integrates system performance with multidimensional analysis. The findings highlight the identification of sensitive attributes and priority interventions, enabling more targeted and effective management strategies for improving the sustainability of communal wastewater treatment systems.